Formation of silver nanoparticles on lignin and two of its precursors - Dahle, Sebastian (Les (Ljubljana), 2021)
Metastable Induced Electron Spectroscopy, Ultraviolet Photoelectron Spectroscopy (He I and He II), X-ray Photoelectron Spectroscopy, and Atomic Force Microscopy were employed to study the interaction of silver with lignin as well as with two of its natural precursors, coniferyl alcohol and sinapyl alcohol. For all three of them, no chemical interaction between the adsorbed silver and the organic substrate was found before contact with air. Nevertheless, silver nanoparticles were found in all three cases after contact with air. Thus, a process of silver nanoparticle formation during the decomposition of the organic molecules is suggested, similar to the previously found catalytic decomposition of cinnamyl alcohol by water in the presence of silver atoms.
Keywords: atomic force microscopy; coniferyl alcohol; koniferil alkohol; les; lignin; metastabilna elektronska spektroskopija; metastable induced electron spectroscopy; mikroskopija na atomsko silo; nanodelci; nanoparticle; rentgenska fotoelektronska spektroskopija; silver; sinapil alkohol; sinapyl alcohol; srebro; ultravijolična fotoelektronska spektroskopija; ultraviolet photoelectron spectroscopy; X-Ray photoelectron spectroscopy